A broadband circularly polarized multi‐beam folded transmitarray antenna. Issue 7 (18th March 2022) - Chen, Jiahong; Li, Guowei; Ge, Yuehe; (David) Chen, Zhizhang; Zhang, Hai
Abstract: The multi‐beam reflectarray and transmitarray (TA) antennas are new antennas that can have wide angular coverage. However, they are generally of large profiles. To address the issue, this article proposes a folded TA antenna of high gain and low profile that can produce circularly polarized (CP) multi‐beams. It consists of a main‐reflector, a TA, and a linearly polarized (LP) planar feeding array. It reflects an incident electromagnetic wave twice and converts polarization three times. It has a metasurface that carries out the broadband LP‐to‐CP conversion. A prototype is developed with a height of 1.8λ at 13 GHz. The experimental results show that the antenna can achieve a scanning range of ±10°, a peak gain of 22 dBi, and an aperture efficiency of 20.8%. It has a 3‐dB axial ratio bandwidth of 2.2 GHz (or 16.6%), covering 12.1–14.3 GHz. It features a low profile, high gain, low cost, and easy integration with communication systems (e.g., MIMO transceiver systems).